Traders from the past: Teodoro Vilardebó, Pedro de Angelis and the trade of bones and documents in the Río de la Plata, 1830-1850 - Podgorny, Irina (Circumscribere International Journal for the History of Science, 2011)
This article analyzes the network of transactions knitted around documents and testimonies of the past. Indispensable to write the history of the Americas, the latter became an essential resource for the survival of the sages in the Río de la Plata area in the 1830s and 1840s. This article, focusing on the circulation and publication of objects originating in the older Viceroyalty of Río de la Plata, is structured around the work of three characters who made a lifestyle out of the trade on papers, antiquities and fossil bones, i.e. the enterprises of Oriental Teodoro Miguel Vilardebó, Neapolitan polygraph Pietro de Angelis and engineer-architect Carlo Zucchi. Such transactions define the practice of history and the sciences in the Americas and they open the door to an immense network of trader of the past that still deserves more thorough studies. This paper is grounded on the analysis of the correspondence between de Angelis and Zucchi, kept at Archivio di Stato di Reggio Emilia and edited by its former director Gino Badini, other primary sources and secondary literature. As a phenomenon transcending the Río de la Plata area, this study is also an essay on the constitution of knowledge in the Americas.